Hemodynamic Responses in Carotid Bifurcation Induced by Enhanced External Counterpulsation Stimulation in Healthy Controls and Patients With Neurological Disorders - Tian, Shuai; Pan, Wei; Peng, Junping; Wang, Hui; Deng, Bin; Liang, Yi; Li, Xinghua; Liu, Huahui; Wang, Yujia; Luo, Bin; Du, Jianhang (Frontiers in Physiology, 2021)
Enhanced external counterpulsation (EECP) is an FDA-approved, non-invasive, assisted circulation therapy for ischemic cardiovascular and cerebrovascular diseases. Previous studies have confirmed that EECP stimulus induces largely different cerebral hemodynamic responses in ischemic stroke patients and healthy controls. However, the underlying mechanisms remain uncertain. We hypothesize that different blood redistributions at the carotid bifurcation may play a key role. Ten subjects were enrolled in this study, including five patients with neurological disorders and five young healthy volunteers as controls. Magnetic Resonance Angiography (MRA) was performed on the carotid artery. All subjects received a single session of EECP treatment with external cuff pressures ranging from 20 kPa to 40kPa. Vascular ultrasound measurements were taken in the common carotid artery (CCA), external carotid artery (ECA) and internal carotid artery (ICA). Three-dimensional patient-specific numerical models were developed to calculate the WSS-derived hemodynamic factors. The results indicated that EECP increased CCA and ECA blood flows in both groups. The ICA blood flow in the patient group exhibited a mean increase of 6.67% during EECP treatment compared with the pre-EECP condition; a mean decrease of 9.20% was observed in the healthy control group. EECP increased the averaged wall shear stress (AWSS) throughout the carotid bifurcation in the patient group; the ICA AWSS of the healthy group decreased during EECP. The oscillatory shear index (OSI) in the ICA increased proportionally with external cuff pressure in both groups. The relative resident time (RRT) was constant or slightly decreased in the CCA and ECA in both groups, but increased in the ICA. We suggest that the benefits of EECP to patients with neurological disorders may partly result from blood flow promotion in the ICA and an increase in WSS at the carotid bifurcation. In healthy subjects, ICA blood flow remains constant during EECP, although the CCA blood flow increases significantly. A relatively low external cuff pressure (20 kPa) is recommended as the optimal treatment pressure for better hemodynamic effects. This study may play an important role in the translation of physiological benefits of EECP treatment in populations with or without neurological disorders.